Relevansi Ajaran Siddhartha Gautama tentang Pengelolaan Harta, Meningkatkan Literasi Keuangan Umat Muda - Wily Andresen; Wilson Tang; Yuni Friska; Romeo Sangputra; Onny Setyawan (Institut Bisnis dan Teknologi Pelita Indonesia, 2026)
This study aims to examine the relevance of Siddhartha Gautama's teachings on wealth management in improving the financial literacy of the younger generation, particularly at the Dharma Loka Temple in Pekanbaru. The research background is based on the gap between financial literacy and financial inclusion levels in Indonesia, as well as the importance of developing the younger generation to manage their finances wisely in the modern era. The method used was a Community Service activity through seminars, lectures, and practical training conducted face-to-face. The material presented covered basic financial management concepts, simple financial record-keeping, the use of digital technology, and financial management based on Buddhist teachings, particularly the Sigalovada Sutta, which emphasizes the wise distribution of wealth. The results of the activity showed an increase in participants' understanding, awareness, and a change in mindset regarding the importance of planned financial management. Participants also began to understand the importance of distinguishing between needs and wants and showed interest in utilizing digital technology for financial management. Overall, this activity made a positive contribution as an initial step in improving the financial literacy of the younger generation based on Buddhist values. Keywords: financial literacy, wealth management, Buddhism, young generation, community service